At-risk gambling in patients with severe psychiatric illness and in community subjects matched for age and sex. (October 2021) - Vita, Antonio; Bastiani, Luca; Turrina, Cesare; Benedetti, Elisa; Bergamini, Annalisa; Molinaro, Sabrina
Highlights: This study matched a large number of psychiatric patients with community controls. The independent effects of alcohol and substance use were also investigated. High-risk gambling in psychiatric patients was four times that of controls. Substance use is an independent major predictor of at-risk gambling. Abstract: In the recent literature the rates of gambling in psychiatric patients have been compared only indirectly with those found in community samples and no study has so far matched a clinical sample with community controls. We selected 875 outpatients attending two community mental health centers and 3.500 community subjects, matched for age and sex. At-risk gambling was defined according to the four categories of the Canadian Problem Gambling Index (CPGI) scores: 0 no-risk, 1-2 low-risk, 3-7 moderate-risk, 8+ high-risk. Data were also collected on substance, alcohol, and tobacco use. Patients were diagnosed with schizophrenia, bipolar disorder, unipolar depression, cluster B personality. At-risk gambling was significantly higher in psychiatric patients compared to community subjects. In the univariate multinomial logistic regression analysis, high-risk gambling was associated with lifetime substance use and being unmarried, moderate-risk with age at onset of alcohol use and lifetime tobacco use, and low-risk with higher education. In the multinomial logistic regression analysis high risk-gambling in psychiatric patients was four times that of community controls, while in substance users high-risk gambling was two times that of non-users. The results suggest that screening for gambling could improve the care of psychiatric patients who suffer from a comorbid behavioral addiction.